Makna Nilai Agama Dalam Keputusan Boikot Produk : Studi Kualitatif Pada Komunitas Muslim dan Non Muslim di Palangka Raya - Suherman, Suherman; Muhammad Farras Nasrida; Dicky Perwira Ompusunggu; Tiur Roida Simbolon; Andhika Pratama (FKIP, Universitas Palangka Raya, 2024)
This study aims to explore the role of religious values, social pressure, and product awareness in the ethical consumption decisions of Muslim and non-Muslim communities in Palangka Raya concerning products associated with Israel. Using a descriptive qualitative approach, the research involves in-depth interviews with respondents from both communities. The findings indicate that ethical consumption decisions among Muslims are influenced by a combination of religious values and social pressure. For them, the decision to boycott certain products reflects both religious beliefs and social solidarity. In contrast, the non-Muslim community demonstrates a more pragmatic approach to consumption decisions, which is primarily based on economic factors such as price and product quality. Social media plays a significant role in disseminating information and reinforcing solidarity among Muslims, whereas the non-Muslim community tends to be more selective in the information they consider on this issue. This study contributes to the understanding of how religious values and social pressures can shape ethical consumption behavior within a diverse religious society.